Telemedicine virtual reality based skin image in children's dermatology medical system. (6th June 2021) - Gao, Juanjuan; Lyu, Chong; Qiao, Xianhua; Tian, Fei
Abstract: At present, with the rapid development of computer and communication technology and people's demand for medical technology services, telemedicine virtual reality technology has become a high‐tech hot spot in the information age and a new trend in the development of the medical industry. However, my country's high‐quality medical resources are mainly concentrated in large and medium‐sized cities, and there is an urgent need to improve the fairness of medical services. Telemedicine virtual reality technology has received more and more attention from people, has been widely used worldwide, and has become an important part of hospital information engineering. This article first introduces the basic concepts of telemedicine virtual reality technology, the latest development of telemedicine virtual reality technology and related technologies, and then introduces the system in detail. The system is functionally divided into two parts: consulting management and system management. Consulting management includes all remote business consulting processes; system management includes management of medical resources and user data, and then detailed description and visualization of the development and use of disease model libraries. Telemedicine completely separates the rehabilitation area of skin patients from the hospital, and patients can complete relief and rehabilitation outdoors or even when they are discharged from the hospital. As a remote access device, telemedicine virtual reality technology has been popularized to a certain extent. The general patient group represented by patients with stable skin conditions has improved their understanding of telemedicine technology, which is beneficial to the development of telemedicine virtual reality technology. The utilization rate, safety, rehabilitation effect and completion rate of telemedicine virtual reality technology are as high as 85%, 92%, and 96%, respectively, saving a lot of time and medical expenses. Therefore, telemedicine virtual reality technology is also the direction of my country's next medical reform, and it can also be used in other aspects of continuing education of telemedicine virtual reality technology.